Teoria crítica e educação: os processos de subjetivação no contexto do declínio da experiência - Roque, Joaquim Iarley Brito (2019)
The present thesis is based on the dialectical confrontation between Critical Theory and Psychoanalysis, theoretical frameworks that intersect to allow a reading about the impacts of the structural modifications caused by capitalism under the individual subjectivation processes and their collective reverberations. As research methodology, the epistemological perspective of the allegory is used, introduced by the German philosopher Walter Benjamin in his work The Origin of German Tragic Drama, which highlights the configuration of a dialectics without synthesis and non-teleological. With basis on the reflections on Social Psychology by Theodor Adorno, Max Horkheimer, Herbert Marcuse, Walter Benjamin, Jean Pierre-Lebrun, Charles Melmam, Slavoj Žižek, among others, an investigation is structured on how the world of life (Lebenswelt) and the work of culture (Kulturarbeit) marked by the generalized crisis of authority, by the intonation of the subject and its consequent estrangement from the prohibitions inherent in collective life, promotes the substitution of a neurotic psychic economy for a perverse one. As a result, this highlights that the transformation of the patriarchal culture into matriarchal favored the emergence of a psychological subject that denies the interdiction of desire and ends up being seduced by the ideology of consumption, which starts to operate as a co-optician of subjectivities through fetishization. We also confirm that the abandonment of the art of narration, a phenomenon caused by the transformation of communal societies into vertical and rationalized ones, has caused the disappearance of the transmissible experiences, negatively impacting the education and the work of subjective elaboration. Finally, the present work proposes to confront the crisis of legitimacy by overcoming educational technicality, which produces an instrumental reason, and by implementing a shaping based on the dimension of the experience of perlaboration (Durcharbeitung), which enables the constitution of a critical reason.